Natural gas combustion furnaces with air and flue gas mixing: Numerical study and industrial application - Zechen Lu; Xiang Li; Zhihao Tang (Case Studies in Thermal Engineering, 2025)
Precise control of the outlet temperature in combustion furnaces is essential for optimizing energy utilization efficiency. This study develops a representative CFD model for a natural gas combustion furnace, considering the heat transfer during the mixing of air and flue gas. The model validation was conducted, with numerical results showing excellent agreement with experimental data. The flow field characteristics of combustion furnaces with three different structures were investigated using the developed CFD model. Based on the simulation results, the optimization schemes are proposed. The simulation results demonstrated that in Case 1, the gases temperature gradients showing a radial increase from the peripheral region to the core zone, resulting in insufficient temperature regulation. For Case 2, the outlet thermal distribution presented significant heterogeneity, accompanied by moderate accuracy in temperature control. In comparison, Case 3 demonstrates that the gas forms a helical flow structure, which helps to promote gas heat exchange, thereby achieving more uniform thermal distribution and superior temperature regulation. Consequently, Case 3 was selected for industrial application. The operational data of commercial scale gas combustion furnaces indicate that the outlet temperature field exhibits a high degree of uniformity, while the emissions of nitrogen oxides meet environmental standards.